The ESL/ELL teacher's survival guide ready-to- use strategies, tools, and activities for teaching English language learners of all levels - Ferlazzo, Larry; Hull-Sypnieski, Katie 1974- (Jossey-Bass teacher, 2022)
"The ESL/ELL Teacher's Survival Guide, 2nd Edition offers educators practical strategies for setting up an ESL-friendly classroom, motivating and interacting with students, communicating with parents of English language learners, and navigating the challenges inherent in teaching ESL students. The second edition includes more than 150 pages of new content, including: A new chapter on working with Long-Term English Language Learners A new chapter on teaching English to students in countries where English is not the primary language A new chapter on Teaching Elementary Age ELLs An updated chapter on Math An updated chapter on Science Revised connections to Common Core Standards Updated research & technology connections Many new instructional strategies and student hand-outs that we were not able to include in The ELL Teacher's Toolbox, including sections on assessment, homework, the summer slide and many more"--Provided by publisher.